TRANSLATION TECHNIQUES OF GARMENT STEAMER PARTS TERMS IN USER MANUAL - Mukminin, Muhamad Saiful (Research on English Language Education, 2025)
This study aims to describe the translation of garment steamer parts terms from English to Indonesian in the user manual. The method used is descriptive qualitative, with data consisting of technical terms related to the parts of the device, both in single words and phrases. The data source is the Philips EasyTouch Plus Garment Steamer user manual, models GC514, GC518, and GC524. The data collection technique employed is the listening and note-taking technique, where the researcher carefully reads the entire text of the manual to identify and record relevant terms. The data analysis follows the interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study show the application of five translation techniques: two single techniques (Compensation and Established Equivalent), and three combined techniques (Compensation + Transposition, Compensation + Borrowing, and Compensation + Established Equivalent). The Compensation technique is the most dominant, appearing 6 times, followed by Established Equivalent with 5 occurrences. These findings indicate that Compensation is frequently used to address linguistic differences between the source and target texts. This study implies that understanding the appropriate translation techniques is crucial for producing translations that are accurate and easily understood.